Investigation of a Multiflow Ejector Equipped with Variable-Length Links for Thrust Vector Control Using Euler’s Methodology - Yuri A. Sazonov; Mikhail A. Mokhov; Anton V. Bondarenko; Victoria V. Voronova; Khoren A. Tumanyan; Egor I. Konyushkov (Eng)
The coordinated operation of multiple jet devices enhances the efficiency of technological processes and thrust vector control systems, enabling the resolution of various practical challenges. Traditional jet control systems regulate the thrust vector in the direction from +20° to −20° in a 3D space. For the first time, this study considers, from a general perspective, the conditions under which the thrust vector angle can vary from +180° to −180° in any direction within a complete geometric sphere, including thrust reversal. Conceptual design using computational fluid dynamics (CFD) techniques considers kinematic schemes with variable lengths and flexible links. This study demonstrates the technical feasibility of controlled energy distribution through multidirectional ejector channels, including the maintenance of constant pressure at the nozzle apparatus inlet. Potential modernization strategies for the Laval nozzle incorporating a rotary diffuser were examined. The research outcomes are patented and aimed at developing a digital twin of the jet system for training artificial intelligence based on the philosophy of science and technology and Euler’s methodology within interdisciplinary works. The findings are primarily applicable to research and development efforts focused on creating energy-efficient oil and gas production systems. Furthermore, the research results can be applied to the development of advanced maneuverable unmanned vehicles and robotics for various purposes.